Orthogonal antiferromagnetism to canted ferromagnetism in CaCo3Ti4O12 quadruple perovskite driven by underlying kagome lattices - Midori Amano Patino; Fabio Denis Romero; Hyun-Joo Koo; Maxim Avdeev; Sean D. A. Injac; Masato Goto; Myung-Hwan Whangbo; Yuichi Shimakawa (Communications Materials, 2022)
Quadruple perovskites are characterized by competing long-range spin interactions that result in complex magnetic structures. Here, the authors synthesize and characterize the magnetic behaviour of CaCo3Ti4O12, suggesting that the observed magnetic structures arise from different ways to avoid frustration in underlying kagome lattices.